Indoor air quality of environments used for physical exercise and sports practice: Systematic review - Andrade, Alexandro (2018)
© 2017 Elsevier LtdBackground Systematic reviews have the potential to contribute substantially to environmental health and risk assessment. Objective This study aimed to investigate indoor air quality of environments used for physical exercise and sports practice through a systematic review. Methods The systematic review followed the PRISMA guidelines and was recorded in the PROSPERO registry (CRD42016036057). The search was performed using the SciELO, Science Direct, Scopus, LILACS, MEDLINE via PubMed, and SPORTDiscus databases, from their inception through April 2017. The search terms used in the databases were {air pollution” OR “air pollutants” OR “air quality”} AND {“physical exercise” OR “physical activity” OR “sport”}. The results of selected studies were divided into 5 categories for analysis: monitoring of air quality in the environment according to international guidelines, indoor-to-outdoor ratio (I/O), air quality during physical exercise, impact of air quality on health, and interventions to improve indoor air quality. Results Among 1281 studies screened, 34 satisfied the inclusion criteria. The monitoring of pollutants was conducted in 20 studies. CO and NO2 were the most investigated pollutants, and guidelines were discussed in most studies. The I/O ratio was investigated in 12 studies, of which 9 showed a higher concentration of some pollutants in indoor rather than outdoor environments. Among the 34 studies selected, only 7 investigated the impact of indoor air pollution on human health. The population in most of these studies consisted of hockey players. Conclusion Most studies conducted monitoring of pollutants in indoor environments used for physical exercise and sports practice. The earliest studies were conducted in ice skating rinks and the most recent evaluated gymnasiums, fitness centers, and sports centers. The CO, particulate matter, and NO2 concentrations were the most investigated and have the longest history of investigation. These pollutants were within the limits established by guidelines in most studies. Studies that examined the association between air quality documented the adverse effects of pollution. There is a need for more studies focused on the relationship between pollution and health.